Justice and reconciliation in Luke 19:1–10: A South African post-apartheid anti-imperial reading - Motuku, Patson K.; van Eck, Ernest (Verbum et ecclesia, 2024)
This article endeavours to offer an anti-imperial interpretation of the micro-narrative of Zacchaeus in Luke 19:1–10, portraying it as a model for justice and reconciliation in post-apartheid South Africa. This analysis stems from the perceived shortcomings of the outcomes of the Convention for a Democratic South Africa (CODESA) negotiations and the Truth and Reconciliation Commission’s (TRC) efforts in nation-building, particularly in the realm of socio-economic justice, which remained unaddressed. The article proposes that an examination of the Greek verbs δίδωμι and άπoδίδωμι in Luke 19:8 within the broader context of the third Gospel – taking into account linguistic, structural and thematic considerations – reveals their inherent futuristic quality. This quality allows for their repetitive usage or usage with a future-oriented intent, seamlessly integrating them into the narrative and supporting an interpretation that depicts Zacchaeus as a repentant sinner committed to reforming his ways. Zacchaeus’s repentant stance, particularly in relation to economic justice, is seen as an essential model for addressing justice for victims of colonialism and apartheid and fostering reconciliation between black people and white people in South Africa.Intradisciplinary and/or interdisciplinary implicationsThe anti-imperial method of reading makes it possible to foreground the imperial narrative and social world(s) of the Bible, analysing the theological critique of the values, structures, institutions and systems of these world(s) by New Testament writers, and applying the same critique to the political and socio-economic structures of colonialism, apartheid, and post-colonial South Africa today. Accordingly, this research intersects with imperial, colonial and post-colonial theories in the disciplines of sociology, history and political science.